On k-swirching of mappings on finite fields - Mikayel G. Evoyan; Gohar M. Kyuregyan; Melsik K. Kyuregyan (Изд-во НАН РА)
The switching construction was used in several recent papers to construct special mappings on ¯nite ¯elds. In this paper we generalize the concept of switching to a k-switching with 1 · k · n. We present some general properties of k-switching and describe permutations produced using k-switching
Keywords: Mathematics